Enhanced intermolecular forces in supramolecular polymer nanocomposites - F. Lin; R. Wang; L. Liu; B. Li; L. W. Ouyang; W. J. Liu (eXPRESS Polymer Letters, 2017)
Ureido-pyrimidone (Upy) can dimerize in a self-complementary array of quadruple hydrogen bonds. In this paper, supramolecular polymer composites were prepared by blending Upy functionalized nanosilica with Upy end-capped polycarbonatediol. Surface characteristics of Upy functionalized nanosilica and influences of supramolecular forces on interfacial binding were researched. Fourier transform infrared spectroscopy (FTIR), Nuclear magnetic resonance (NMR) and Gel permeation chromatography (GPC) were used to characterize the synthesized molecules. Grafting ratio of Upy segments on the surface of nanosilica was analysed by Thermogravimetic analysis (TGA). Hydrophobicity and morphology of Upy modified nanosilica were analysed by Contact angle tester and Scanning electron microscope (SEM). Furthermore, dynamic thermo mechanical properties, mechanical properties and distribution of nanosilica in supramolecular polymer composites were also researched. Compared with the matrix resin, tensile stress and young's modulus of supramolecular polymer composites containing 5 wt% modified nanosilica were increased by 292 and 198% respectively.